Synchroton radiation of self-collimating relativistic magnetohydrodynamic jets - Porth, Oliver; Fendt, Christian; Meliani, Zakaria; Vaidya, Bhargav (The astrophysical journal, 2011)
The goal of this paper is to derive signatures of synchrotron radiation from state-of-the-art simulation models of collimating relativistic magnetohydrodynamic (MHD) jets featuring a large-scale helical magnetic field. We perform axisymmetric special relativistic MHD simulations of the jet acceleration region using the PLUTO code. The computational domain extends from the slow-magnetosonic launching surface of the disk up to 60002 Schwarzschild radii allowing jets to reach highly relativistic Lorentz factors. The Poynting-dominated disk wind develops into a jet with Lorentz factors of Γ ≃ 8 and is collimated to 1°. In addition to the disk jet, we evolve a thermally driven spine jet emanating from a hypothetical black hole corona. Solving the linearly polarized synchrotron radiation transport within the jet, we derive very long baseline interferometry radio and (sub-) millimeter diagnostics such as core shift, polarization structure, intensity maps, spectra, and Faraday rotation measure (RM) directly from the Stokes parameters. We also investigate depolarization and the detectability of a λ2-law RM depending on beam resolution and observing frequency. We find non-monotonic intrinsic RM profiles that could be detected at a resolution of 100 Schwarzschild radii. In our collimating jet geometry, the strict bimodality in the polarization direction (as predicted by Pariev et al.) can be circumvented. Due to relativistic aberration, asymmetries in the polarization vectors across the jet can hint at the spin direction of the central engine.
Gesehen am 12.01.2023